Pengembangan Modul Ajar Kurikulum Merdeka Topik Usaha Energi Berbasis Inkuiri Terintegrasi Keterampilan Kolaborasi - Yurike Yiniar; Endang Lovisia; Yaspin Yolanda (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2024)
The problem in this study is how to create a learning tool that is able to increase the knowledge and skills of students and be able to increase the interest of students in participating in learning. The objectives of this study were (1) to develop teaching tools in the form of inquiry-based teaching modules, (2) to improve collaboration skills and (3) to improve students' communication skills after using inquiry-based teaching modules in learning effort and energy. This research is a development research using the 4D development model. The subjects of this research were students of class XI MAN 2 Lubuklinggau. The data collection technique used is in the form of validation sheets, and skill observation sheets. Validation obtained based on three validators, namely media experts 51, linguists 73 and material experts 47. Thus, the inquiry-based teaching module is very feasible to use as a learning tool. The results of collaboration skills amounted to 0.71 with a high category, while communication skills amounted to 0.74 with a high category. Based on the research conducted according to the data obtained, the development of inquiry-based teaching modules can improve collaboration skills and communication skills so that it is feasible to use in learning.